2011
DOI: 10.1021/mp200426h
|View full text |Cite
|
Sign up to set email alerts
|

SPANosomes as Delivery Vehicles for Small Interfering RNA (siRNA)

Abstract: Non-ionic surfactant vesicles, or SPANosomes (SPs), comprised of cationic lipid and sorbitan monooleate (Span 80) were synthesized and evaluated as siRNA vectors. The SPs had a mean diameter of less than 100 nm and exhibited excellent colloidal stability. The SP/siRNA complexes possessed a slightly positive zeta potential of 12 mV and demonstrated a high siRNA incorporation efficiency of greater than 80%. Cryogenic transmission electron microscopy (cryo-TEM) imaging of the SP/siRNA indicated a predominantly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 50 publications
0
49
0
Order By: Relevance
“…Here, the release of siRNA from G5 PD dendrimer was measured using a molecular beacon (MB), as a siRNA mimic. A MB is an oligodeoxynucleotide that has a stem-and-loop structure with a fluorophore on one end and a quencher on the other (14,21,22). When the MB binds to the target mRNA sequences in the cytosol, it becomes fluorescent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the release of siRNA from G5 PD dendrimer was measured using a molecular beacon (MB), as a siRNA mimic. A MB is an oligodeoxynucleotide that has a stem-and-loop structure with a fluorophore on one end and a quencher on the other (14,21,22). When the MB binds to the target mRNA sequences in the cytosol, it becomes fluorescent.…”
Section: Resultsmentioning
confidence: 99%
“…After 24 h of incubation, cells were treated with medium, or media containing sucrose (0.4 M), cytochalasin D (cyto D, 5 μM), or nystatin (50 μM) for 1 h. NPs composed of G5 PD dendrimer and FAM-siRNA and Cy3-MB were then added and the cells were incubated for 1 h (14). The cells were then washed twice with PBS and treated with 0.25% trypsin/ EDTA for 2 min at 37°C for detachment, followed by fixation in 4% formalin.…”
Section: Methodsmentioning
confidence: 99%
“…Small interfering RNA (siRNA) technology has been used to inhibit transcription of hepatitis G virus (Cao et al, 2005), influenza virus (Ge et al, 2003), picorna virus (Lim et al, 2008) and trypanosma brucei . SiRNA molecular beacons have been used successfully in the detection and knockdown of telomerase expression in human breast cancer cells (Chang et al, 2007), BMP4 mRNA in hedgehog signaling (Rhee et al, 2008) and aromatase mRNA in breast cancer cells (Zhou et al, 2011). SiRNA technology has been tested successfully for imaging and silencing genes in M. tuberculosis (Harth and Horwitz, 1999;Li et al, 2007) and for inhibiting bacterial growth in human macrophages infected with M. tuberculosis (Harth et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we devised a cationic niosome using Span 80, a cationic lipid DOTAP and TPGS, which could efficiently achieve simultaneous DOX encapsulation and siRNA complexation. Here, Span 80 functions as the main component to form niosomes and, more importantly, to facilitate efficient siRNA delivery by destabilizing endosomal membrane and subsequent release in the cytoplasm [26,27]. From the cell studies, we observed a simultaneous delivery of DOX and siRNA inside the 231-CSCs.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, we added DOTAP as helper lipid into Span80-based niosome to render its ability for siRNA loading. More importantly, recent studies showed that cationic niosomes are highly potent gene delivery carriers by promoting endosomal escape and transport of payload to cytoplasm [26,27]. Therefore, our system is a new type of cationic niosome for co-delivery of drug and siRNA.…”
Section: Introductionmentioning
confidence: 93%